2021
DOI: 10.33715/inonusaglik.987625
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Melatonin Content and Antioxidant Capacity in Grape Berries

Abstract: In this study, six berry fruits; goji berry/wolfberry (Lycium barbarum), black mulberry (Morus nigra), white mulberry (Morus alba), blackberry (Rubus fructicous L.), purple mulberry (Morus rubra) and Bursa Black mulberry (unknown) were analyzed by HPLC-FD to determine whether they present melatonin. The melatonin was detected different amounts in all samples. Besides, the total phenolic content and antioxidant capacity were studied in all fruit samples. DPPH and ABTS tests were applied to determine the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…Melatonin, a hormone primarily associated with regulating sleep–wake cycles, has been identified in various plant sources, including goji berries. Studies have shown that goji berries contain significant levels of melatonin, although the exact concentration may vary depending on factors such as growing conditions, maturity at harvest, and post-harvest handling [ 116 ].…”
Section: Bioactive Composition Of L Barbarummentioning
confidence: 99%
“…Melatonin, a hormone primarily associated with regulating sleep–wake cycles, has been identified in various plant sources, including goji berries. Studies have shown that goji berries contain significant levels of melatonin, although the exact concentration may vary depending on factors such as growing conditions, maturity at harvest, and post-harvest handling [ 116 ].…”
Section: Bioactive Composition Of L Barbarummentioning
confidence: 99%
“…2 Tanaman murbei memiliki kandungan antioksidan yang baik untuk kesehatan pada buah dan daunnya. 3,4 Selain itu, bahan aktif daun murbei dapat digunakan untuk mengobati beberapa penyakit, seperti hipertensi, diabetes, hiperlipidemia, dan sebagai imunomodulasi. 5 Pengembangan dan penelitian berbasis tanaman ini sangat diperlukan karena sumber bahan alamnya tersedia banyak diwilayah Indonesia.…”
Section: Pendahuluanunclassified